Modulation of Butyrate Anticancer Activity by Solid Lipid Nanoparticle Delivery: An in Vitro Investigation on Human Breast Cancer and Leukemia Cell Lines - Federica Foglietta; Loredana Serpe; Roberto Canaparo; Nicoletta Vivenza; Giovanna Riccio; Erica Imbalzano; Paolo Gasco; Gian Paolo Zara (Frontiers Media S.A., 2014)
Purpose. Histone modification has emerged as a promising approach to cancer therapy. The short-chain fatty acid, butyric acid, a histone deacetylase (HD) inhibitor, has shown anticancer activity. Butyrate transcriptional activation is indeed able to withdraw cancer cells from the cell cycle, leading to programmed cell death. Since butyrate's clinical use is hampered by unfavorable pharmacokinetic and pharmacodynamic properties, delivery systems, such as solid lipid nanoparticles (SLN), have been developed to overcome these constraints. Methods. In order to outline the influence of butyrate delivery on its anticancer activity, the effects of butyrate as a free (sodium butyrate, NB) or nanoparticle (cholesteryl butyrate solid lipid nanoparticles, CBSLN) formulation on the growth of different human cancer cell lines, such as the promyelocytic leukemia, HL-60, and the breast cancer, MCF-7 was investigated. A detailed investigation into the mechanism of the induced cytotoxicity was also carried out, with a special focus on the modulation of HD and cyclin-dependent kinase (CDK) mRNA gene expression by real time PCR analysis. Results. In HL-60 cells, CBSLN induced a higher and prolonged expression level of the butyrate target genes at lower concentrations than NB. This led to a significant decrease in cell proliferation, along with considerable apoptosis, cell cycle block in the G0/G1 phase, significant inhibition of total HD activity and overexpression of the p21 protein. Conversely, in MCF-7 cells, CBSLN did not enhance the level of expression of the butyrate target genes, leading to the same anticancer activity as that of NB. Conclusions. Solid lipid nanoparticles were able to improve butyrate anticancer activity in HL-60, but not in MCF-7 cells. This is consistent with difference in properties of the cells under study, such as expression of the TP53 tumor suppressor, or the transporter for short-chain fatty acids, SLC5A8.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page. Purpose. Histone modification has emerged as a promising approach to cancer therapy. The short-chain fatty acid, butyric acid, a histone deacetylase (HD) inhibitor, has shown anticancer activity. Butyrate transcriptional activation is indeed able to withdraw cancer cells from the cell cycle, leading to programmed cell death. Since butyrate's clinical use is hampered by unfavorable pharmacological pharmacokinetic and pharmacodynamicproperties, delivery systems, such as solid lipid nanoparticles (SLN), have been developed to overcome these constraints. Methods. In order to outline the influence of butyrate delivery on its anticancer activity, the effects of butyrate as a free (sodium butyrate, NB) or nanoparticle (cholesteryl butyrate solid lipid nanoparticles, CBSLN) formulation was investigated on the growth of different human cancer cell lines, such as the promyelocytic leukemia, HL-60, and the breast cancer, MCF-7 was investigated. A detailed investigation into the mechanism of the induced cytotoxicity was also carried out, with a special focus on the modulation of HD and cyclin-dependent kinase (CDK) mRNA gene expression by real time PCR analysis. Results. In HL-60 cells, CBSLN induced a higher and prolonged expression level of the butyrate target genes at lower concentrations than NB. This led to a significant decrease in cell proliferation, along with considerable apoptosis, cell cycle block in the G0/G1 phase, significant inhibition of total HD activity and overexpression of the p21 protein. Conversely, in MCF-7 cells, CBSLN did not enhance the level of expression of the butyrate target genes, leading to the same anticancer activity as that of NB. Conclusions. Solid lipid nanoparticles were able to improve butyrate anticancer activity in HL-60, but not in MCF-7 cells. This is consistent with the difference in cells' properties of the cells under study, such as expression of the TP53 tumor suppressor, or the transporter for short-chain fatty acids, SLC5A8.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page. <w:LsdException Locked="false"